From Access to Instructional Design: Indonesian Senior High School Students’ Digital Pedagogy Experiences, Barriers, and Improvement Priorities - Septi Purfitasari; Masrukhi Masrukhi; Titi Prihatin; Sungkowo Edy Mulyono (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2026)
School-based digital pedagogy has expanded rapidly, yet prior research has often examined it through access, platforms, or adoption rather than through an integrated account of students’ experiences, barriers, instructional support, and improvement priorities. This study investigated digital pedagogy among 403 students in Grades 10, 11, and 12 at a public senior high school in Central Java, Indonesia, selected through random sampling from a population of 1,173 students. A cross-sectional descriptive survey was conducted within a convergent mixed-methods design using a questionnaire that combined closed-ended and open-ended items; the closed-ended instrument showed acceptable internal consistency (Cronbach’s alpha = 0.82). Quantitative data were analysed using descriptive statistics, multi-response analysis, ranking analysis, and composite scores, while qualitative responses were analysed through open, axial, and selective coding. The findings showed that students had strong baseline access, with smartphone use reaching 99.3% and personal device ownership 98.5%, but participation remained predominantly mobile-based and was constrained by unstable connectivity, limited quota, workload pressure, and technical problems. Digital pedagogy was mainly organised around videos, assignments, presentations, and quizzes, whereas discussion-based and simulation-rich activities were much less common. Students generally experienced digital pedagogy as functional but not yet strongly transformative across implementation exposure, perceived benefit, obstacle, and instructional support. Open-ended responses identified access to materials and relearning as the most helpful experience, while connectivity and access problems emerged as the most disruptive barriers. The study concludes that improving school digital pedagogy requires not only stronger infrastructure but also clearer instructional design to convert access into meaningful and equitable learning experiences.